Difficulties and Solutions in Substantive Merger Bankruptcy of Affiliated Enterprises - Lu, Yufan (International Journal of Global Economics and Management, 2024)
This paper provides an in-depth analysis of the theoretical foundation and practical implementation of the substantive merger bankruptcy system for affiliated enterprises, highlighting its significance and challenges in the contemporary economic environment. Through a comprehensive examination of the legal basis, value function, and current legal and judicial status of substantive merger bankruptcy, this study uncovers key issues in its execution while putting forward recommendations for improvement in legislation and judicial practice. The research emphasises the necessity to clarify legal standards, optimise creditor protection mechanisms, and implement appropriate commencement modes to improve efficiency, fairness, and transparency in insolvency proceedings, support the effective restructuring of complex enterprise clusters and ensure market stability.